2023
DOI: 10.1021/acsanm.2c04262
|View full text |Cite
|
Sign up to set email alerts
|

Au–WS2 Nanohybrids with Enhanced Optical Nonlinearity for Optical Limiting Applications

Abstract: Utilizing plasmonic effects of metal nanostructures on tailoring the properties of semiconducting materials has gained substantial research attention in the past 10 years. Here, we report the plasmon resonance-induced enhanced optical nonlinearity of Au−WS 2 nanohybrids prepared via the blending of liquid phase exfoliated few-layer WS 2 nanosheets with chemically synthesized spherical gold nanoparticles (NPs). Nonlinear optical properties were studied using the open aperture Z-scan technique with nanosecond la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…This nonlinear absorption coefficient is three orders of magnitude stronger than the reported value of Au/ZnO arrays 38 and six orders of magnitude stronger than comparative results reported in Au/WS 2 nanohybrids. 39 Saturable absorption is demonstrated by pure 2D MoS 2 , as confirmed by Wang et al, 40 and according to Abhijith et al 41 Au-WS 2 nanohybrids created by combining liquid-phase exfoliated few-layer WS 2 nanosheets with chemically generated spherical gold nanoparticles (NPs) exhibit improved optical nonlinearity induced by Plasmon resonance. They reported enhanced reverse saturable absorptions.…”
Section: Nonlinear Optical Propertiesmentioning
confidence: 72%
“…This nonlinear absorption coefficient is three orders of magnitude stronger than the reported value of Au/ZnO arrays 38 and six orders of magnitude stronger than comparative results reported in Au/WS 2 nanohybrids. 39 Saturable absorption is demonstrated by pure 2D MoS 2 , as confirmed by Wang et al, 40 and according to Abhijith et al 41 Au-WS 2 nanohybrids created by combining liquid-phase exfoliated few-layer WS 2 nanosheets with chemically generated spherical gold nanoparticles (NPs) exhibit improved optical nonlinearity induced by Plasmon resonance. They reported enhanced reverse saturable absorptions.…”
Section: Nonlinear Optical Propertiesmentioning
confidence: 72%
“…The selected area diffraction pattern (SAED) shown in the inset of Figure a confirms the polycrystalline nature of nanosheets. The detailed study on the morphology of WS 2 nanosheets, such as estimating the physical thickness, ensuring the uniform dispersity in thickness, and identifying the number of layers, were included in our earlier reports. , These studies revealed that present nanosheets exhibited a thickness around 2–4 nm that corresponds to a few layers, which is highly beneficial for utilizing these materials in the fabrication of OSCs, as reported by Lin et al Figure b,c shows the TEM and FE-SEM images of Au-WS 2 nanohybrids, respectively, where the WS 2 nanosheets were found to be uniformly decorated with the different shapes of isolated Au nanostructures.…”
Section: Results and Discussionmentioning
confidence: 92%
“…Each Au nanostructure presented unique near-field effects, which significantly enhanced field intensity within the active layer. Additionally, more than 50% forward scattering occurred, making these plasmonic nanostructures suitable for enhancing photosensitivity and increasing absorption density in the system 22 . Loading mixed AuNPs, composed of bone-like rod shapes, cubes, and irregular spheres, into the PEDOT:PSS layer significantly improves the photovoltaic performance of the PTB7:PC 71 BM-based solar cell by 9.26%.…”
Section: Arinze Et Al Simulated a Model Involving Different Shapes Ofmentioning
confidence: 99%
“…These nanostructures were strategically positioned not only within the active, hole transport, and buffer layers but also at their interfaces, leading to heightened solar cell efficiency. The utility of achieving multiple plasmonic excitations or tuning plasmonic activity has been demonstrated through the combination of different shapes of AuNPs [21][22][23]33 . Mixing shapes, such as spheres with rods, spheres with bipyramids, and hybrid configurations, have been reported, leveraging the cooperative effects of distinct plasmonic excitations arising from the combination of AuNP morphologies 20 .…”
Section: Introductionmentioning
confidence: 99%